Notes on the genus Silene (Caryophyllaceae, Sileneae) in Iran - Jafari, Farzaneh; Mirtadzadini, Mansour; Gholipour, Abbas; Rabeler, Richard; Oxelman, Bengt; Zarre, Shahin (Phytotaxa, 2019)
Two new species―Silene orientoalborzensis and S. circumcarmanica―are here described from Northeast and South Iran, respectively. They belong to Silene subg. Silene sect. Auriculatae which is the largest section of the genus in W-Asia. A specimen from center of Iran, which was identified erroneously as S. atocioides, is revised and identified as S. pendula which represents a new record for the Iranian flora. S. simsii is proposed as a nomen novum for Cucubalus multifidus.